Evaluation of Separate and Combined Effects of Choline and Betaine in Diets for Male Broilers - Waldroup, P.W.; Fritts, C.A. (International Journal of Poultry Science, 2005)
A study was conducted to evaluate the effects of supplementation of corn-soybean meal based diets with betaine and choline on live performance and breast meat yield of male broiler chicks. Diets formulated to meet nutrient levels of top broiler companies were supplemented with either 0 or 1000 mg/kg betaine in combination with either 0 or 1000 mg/kg choline. Betaine supplementation was carried out either for the full 49 d feeding trial or initiated at 35 d of age. Each dietary treatment was assigned to eight replicate pens of 60 male chicks of a commercial strain. At 42 and 49 d of age samples of birds were processed under commercial conditions and dressing percentage and breast yield determined. The results of this study indicate little or no positive benefit in terms of body weight gain, feed conversion, or mortality from the addition of betaine to nutritionally adequate corn-soybean meal based diets for broiler chicks in situations where disease challenge from coccidiosis is not a major issue. Improvements in dressing percentage were obtained from betaine supplementation and in breast yield from choline supplementation at 42 d of age but not at 49 d of age. Therefore, age of bird might be a consideration for using these supplements as birds processed at younger ages might be more responsive to these nutrients. Further studies are needed to evaluate the potential effect of age on response to choline and betaine.